1999
DOI: 10.1007/s11663-999-0093-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for electrochemical nature of the reaction between iron oxide in calcia-silica-alumina slag and carbon in liquid iron

Abstract: The electrochemical nature of the reaction between iron oxide in calcia-silica-alumina slag and carbon in liquid iron has been studied by measuring the kinetics of the slag-metal reaction. A base slag (48 pct CaO-40 pct SiO 2 -12 pct Al 2 O 3 ) containing iron oxide (Յ8 wt pct FeO t ) was reduced by an Fe-C metal bath (ϳ4 wt pct C) at 1400 ЊC. The reaction rate was calculated from measurements of the total inlet gas flow rate and the CO concentration in the outlet gas stream. The slag was "internally short cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 5 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Some researchers have suggested that the reactions between slag and molten alloys are electrochemical in nature. [26][27][28][29][30] These findings, along with the evidence of the role of electrons in the mass transfer of oxygen through slag, [31,32] suggest that, for some reactions, the kinetics can be controlled by electronic transport in slag.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have suggested that the reactions between slag and molten alloys are electrochemical in nature. [26][27][28][29][30] These findings, along with the evidence of the role of electrons in the mass transfer of oxygen through slag, [31,32] suggest that, for some reactions, the kinetics can be controlled by electronic transport in slag.…”
Section: Introductionmentioning
confidence: 99%
“…The above observation proves that the cathodic reaction actually takes place at the wall of the iron crucible. Recently, Woolley et al 25) studied the reduction kinetics of CaO-SiO 2 -Al 2 O 3 slags containing up to 8 wt% FeO, and reported that the reduction of iron oxide from slag by carbon in iron occurs as separate anodic and cathodic reactions; the locations of these reactions may be physically separated by macroscopic distances, and hence the overall reaction is an electrochemical reaction.…”
Section: (7)mentioning
confidence: 99%
“…When DC current passes through the molten slag from the molten metal and then pass to DC-arc or the top graphite electrode, electrolysis occurs at both the metal-slag interface and the slag-gas interface or top graphite. The existence and effects of the electrolysis in steel melting and refining are dependent on whether the nature of the reaction is electrochemical and whether the DC electric current pass through the slag-metal interface [8][9][10][11][12][13][14][15][16]. What will be the effect on the yield of alloy elements if the high manganese TWIP steel is melted with the DC-arc furnace?…”
Section: Introductionmentioning
confidence: 99%